Academic Experiences of Indonesia Student Exchange in the Philippines on Speaking Anxiety: A Narrative Inquiry - Muhammad Subhan Jagad; Andi Rachmawati Syarif; Faridawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to look into the social experiences of students in the seventh semester of Universitas Muhammadiyah Kendari's English language education program who have completed the International Credit Transfer program at Nueva Ecija University of Science and Technology in the Philippines. A Narrative Inquiry research design was used to conduct the study. The participants of this study are four students. Two of the four students are male, while the other two are female. To gather information on students' experiences with speaking anxiety, an extensive narrative interview technique was utilized. Data analysis followed Clandinin and Cain’s (2008), transcript using a three-dimensional framework of narrative inquiry: the dimensions of time, person-social, and place.